Reductive dissolution and release of arsenic from arsenopyrite by a novel arsenate-respiring bacterium from the arsenic-contaminated soils. (September 2019) - Kawa, Yahaya Kudush; Wang, Jianing; Chen, Xiaoming; Zhu, Xianbin; Zeng, Xian-Chun; Wang, Yanxin
Abstract: It is well established that arsenopyrite can be dissolved by both oxygen and microbes under oxic conditions; however, little is known about whether it can be mobilized under anoxic conditions. Here, we isolated a dissimilatory arsenate-respiring prokaryote (DARP) strain ( Citrobacter sp. A99) from arsenic-contaminated soils. It respires arsenate, ferric iron and thiosulfate, but not sulfate. Molecular features of A99 suggest that it is a new DARP. A99 can promote the dissolution and release of arsenic from arsenopyrite, and addition of sulfate enhanced the microbial dissolution of arsenic. SEM/EDS analysis suggested that the bioreduction led to marked changes in the mineral structure, and the residual grains contained much lower contents of arsenic compared to wild-type minerals. Based on the findings of this work, a mechanic hypothesis was proposed to explain the reductive dissolution of arsenopyrite catalyzed by A99 cells. This work suggests that arsenopyrite can be significantly reduced and dissolved by indigenous DARPs under anaerobic conditions. Graphical abstract: Image 1 Highlights: As(V)-respiring bacterium catalyzed reductive dissolution of arsenopyrite. The dissolution of arsenopyrite could be initiated by the reduction of Fe(III). Sulfate promoted the microbial dissolution of arsenopyrite. The microbial reduction and dissolution of arsenopyrite were verified by SEM-EDS analysis. This work deepens our understanding of the formation of As-contaminated groundwater.